Pengaruh Kepemimpinan Transformasional terhadap Kinerja Guru dengan Motivasi sebagai Variabel Intervening pada SMP Negeri 21 Kota Jambi - Wawan Setia Nugraha; Sumarni Sumarni; Rts. Ratnawati (Global Leadership Organizational Research in Management, 2024)
This research is to investigate how transformational leadership affects the performance of teachers, with motivation serving as an intervening factor, at State Junior High School 21 in Jambi City. This study employs quantitative approaches, utilizing questionnaire distribution as the data collection method among 30 participants. Hypothesis testing uses Descriptive Analysis Techniques using the SmartPLS application as a data processing tool. The results of this research indicate that Transformational Leadership has a significant positive influence on the Performance of State Junior High School 21 in Jambi City. Transformational Leadership has a significant positive effect on Motivation. Motivation has a significant positive effect on teacher performance. Transformational Leadership has a significant positive effect on Teacher Performance through Motivation as an intervening variable. Suggestions in this research: (1) In the performance variable, teachers are advised to improve performance by holding discussion sessions at the end of learning hours and providing feedback while teaching. (2) In the transformational leadership variable, it is recommended that school principals can make all teachers feel appreciated, namely by paying attention to all teachers and conveying a sense of understanding to each teacher. (3) In the motivation variable, it is recommended to provide support to teachers, namely the principal by providing awards, and the principal is able to provide a comfortable and conducive work environment.